2015
DOI: 10.1177/0192623315599256
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Carcinomas in Tetrabromobisphenol A–exposed Wistar Han Rats Harbor Increased Tp53 Mutations and Mimic High-grade Type I Endometrial Carcinomas in Women

Abstract: Endometrial carcinoma is the most common gynecologic malignancy is the United States, and accounts for 6% of all cancers in women. The disease is classified as Type I or Type II based on clinicopathologic and molecular features. It is a multifactorial disease with a number of risk factors, including environmental exposures. How environmental exposures, such as flame retardants, may affect the incidence of endometrial cancer is a topic of current and ongoing interest. Tetrabromobisphenol A (TBBPA) is a widely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…DecaBDE was also proposed in 2013 for inclusion in the Convention as it was considered to meet the screening criteria for persistence, bioaccumulation, long-range transport and adverse effects13. Other compounds such as tetrabromobisphenyl A (TBBPA) and hexabromobenzene are accumulating proofs about their toxicity141516, thus such chemicals have a great chance to be proscribed in the next years.…”
mentioning
confidence: 99%
“…DecaBDE was also proposed in 2013 for inclusion in the Convention as it was considered to meet the screening criteria for persistence, bioaccumulation, long-range transport and adverse effects13. Other compounds such as tetrabromobisphenyl A (TBBPA) and hexabromobenzene are accumulating proofs about their toxicity141516, thus such chemicals have a great chance to be proscribed in the next years.…”
mentioning
confidence: 99%
“…Further studies were done to confirm the activated receptor expression levels of phosphorylated EGFR, ERBB2, and IGF1R observed in uterine samples at PND 90 due to their importance in endometrial cancer in women and reported increases in mRNA expression of Erbb2 in TBBPA-induced tumors from rats in the NTP 2-year bioassay 14 and Igf1 growth factor expression in adult rat uteri following TBBPA administration. 17 Western blot analysis was conducted to confirm the expression of activated EGFR, ERBB2, and IGF1R at PND 90 for all groups (Figure 5).…”
Section: (A))mentioning
confidence: 98%
“…13 Epidermal growth factor receptor 2 (HER2: ERBB2), a known regulator of cell proliferation and antiapoptotic pathways, was shown to be increased in TBBPAinduced uterine endometrial carcinomas taken from Wistar Han rats in a 2-year NTP bioassay. 14 Additionally, insulinlike growth factor 1 (Igf1) gene expression was found to be increased in uteri following short-term (5 days) TBBPA (250 mg/kg) exposures in adult rats, 15 and IGF1 is known to be involved in tumorigenesis through RTK signaling pathways. 16 In this study, we were interested in determining the effects of TBBPA on activation of growth factor RTKs following in utero and early-life exposures in Wistar Han rats.…”
Section: Introductionmentioning
confidence: 99%
“…The literature search identified a carcinogenicity study of TBBPA by the US NTP (NTP, 2014), and associated published studies that evaluated these NTP (2014) tumor findings and the TBBPA cancer MOA (Dunnick et al, 2015;Hall, Coulter, Knudsen, Sanders, & Birnbaum, 2017;Harvey et al, 2015;Lai, Kacew, & Dekant, 2015;Sanders et al, 2016;Wikoff et al, 2015;Wikoff et al, 2016). These data are pertinent because the lack of cancer data was identified as a data gap precluding the development of a cancer potency value by regulatory agencies (EFSA, 2011;Health Canada, 2013 However, we did not request this information.)…”
Section: Derivation Of No-significant-risk-levelmentioning
confidence: 99%
“…In the NTP 2-year TBBPA bioassay, and as evaluated by Wikoff et al (2015), uterine tumors in rats were identified as the most appropriate endpoint for use in derivation of a cancer toxicity value. Based on the considerable amount of evidence that TBBPA is not mutagenic, a non-linear MOA was postulated for TBBPA-induced uterine tumors based on interference with estrogen metabolism, as discussed by several authors (Borghoff, Wikoff, Harvey, & Haws, 2016;Dunnick et al, 2015;Hall et al, 2017;Harvey et al, 2015;Lai et al, 2015;Sanders et al, 2016;Wikoff et al, 2015), most comprehensively by Wikoff et al (2016). The interference with estrogen is not thought to involve TBBPA binding directly to the estrogen receptor (ER).…”
Section: Tetrabromobisphenol a Uterine Cancer Mode Of Action And Wementioning
confidence: 99%